Frequency Regulation Provision Using Cross-Brand Bidirectional V2G-Enabled Electric Vehicles - Hashemi, Seyedmostafa; Arias, Nataly Banol [UNESP]; Bach Andersen, Peter; Christensen, Bjoern; Traholt, Chresten (Institute of Electrical and Electronics Engineers (IEEE), 2018)
With the increasing number of electric vehicles (EVs) in use, concern about their impact on the power quality of local distribution grids is also increasing. However, efficient control of state-of-the-art EVs and their supply equipment has a great potential not only to minimize the grid impact from EV integration, but also to provide desired services for system operators in renewable-based energy systems. This paper presents and analyzes the results from the demonstration of frequency-controlled normal operation reserve (FCR-N) that is among the primary frequency regulation services in the Nord Pool energy market. EVs from different EV manufacturers as well as advanced bidirectional DC chargers are implemented in the demonstration, which is the first vehicle-to-grid (V2G) demonstration in the Nordic area with commercially available components and cross-brand EVs. A centralized control method is implemented, and two-way communications links are established to send the control signals and receive the measured data on a second-by-second basis. The results associated with the operation of EVs with different battery capacities providing FCR-N are presented, and several parameters required for validating the quality of support for FCR-N are discussed based on the demonstration outcomes. The results confirm that V2G-enabled EVs are able to provide high quality and very fast responses, and pave the way for future renewable-based energy systems.
Keywords: Demonstration; Electric vehicle; Frequency regulation; Frequency reserve; Vehicle to grid